(untitled) (Research, Society and Development, 2021)
Leishmaniasis is an endemic disease in Goiás and has high lethality owing to its high zoonotic potential. In dogs, the disease manifests based on the parasitic load, with clinical presentation as the starting for diagnosis. Diagnostic methods are used to confirm the disease, with emphasis on lymph node aspiration cytology, which is a high-standard technique owing to its low cost, ease of performance, and high specificity. The aim of this study was to demonstrate aspiration lymph node cytology as a diagnostic method for canine visceral leishmaniasis (CVL) in areas containing low-income populations with poor access to molecular tests. Three dogs with suspected CVL were studied at Veterinary Hospital of the Federal University of Jataí, in which popliteal lymph node cytology was performed, owing to easy access, and screening and confirmatory examinations were undertaken by the Central Public Health Laboratory. The results showed three positive animals in the cytology and only one positive in the other tests; therefore, there was the possibility of the occurrence of false negatives in serological tests given the time required for seroconversion. Thus, cytology is an important diagnostic technique in areas where molecular tests are not available.